2019
DOI: 10.1111/apa.15041
|View full text |Cite
|
Sign up to set email alerts
|

School‐based study showed a correlation between physical activity and smartphone and tablet use by students aged eight, 11 and 14

Abstract: Aim This study investigated correlations between objectively measured physical activity (PA) and smartphone and tablet usage by sex and age in subjects aged eight, 11 and 14. Methods We recruited 549 children and adolescents (264 boys) from six schools in three middle‐class communities in south‐eastern Sweden. Steps per day were objectively measured using sealed pedometers and a brief daily questionnaire about smartphone and tablet usage. Correlations between mean steps per day and mean daily minutes of smartp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 17 publications
1
12
0
Order By: Relevance
“…For Sweden, the average time spent daily on these devices was 2 hours and 47 minutes (second highest after the UK), while playing outdoors (across weekends and weekdays) was only 1 hour and 56 minutes. For the age group 14‐16 years, the time spent on connected mobile devices was 3 hours and 14 minutes, quite similar numbers to those reported by Raustorp for the oldest age group . One must remember that a fair share of this time has probably been ‘stolen’ from the TV and other indoor activities.…”
supporting
confidence: 75%
See 2 more Smart Citations
“…For Sweden, the average time spent daily on these devices was 2 hours and 47 minutes (second highest after the UK), while playing outdoors (across weekends and weekdays) was only 1 hour and 56 minutes. For the age group 14‐16 years, the time spent on connected mobile devices was 3 hours and 14 minutes, quite similar numbers to those reported by Raustorp for the oldest age group . One must remember that a fair share of this time has probably been ‘stolen’ from the TV and other indoor activities.…”
supporting
confidence: 75%
“…In this issue of Acta Paediatrica, Raustorp et al publish a study indicating a negative association between high use of smartphones and tablets and physical activity. 8 The study included 550 students aged 8 to 14, who self-reported their time spent with smartphones and tablets during 4 consecutive weekdays in 2017 while wearing accelerometers to measure steps per day. The authors found a moderately inverse correlation between mean steps per day and mean daily minutes of smartphone and tablet usage.…”
Section: Smartphones-the Good the Bad And The Ugly Consequences Of Usementioning
confidence: 99%
See 1 more Smart Citation
“…This 'all day online accessibility' would be possible via mobile smartphone use, and children aged 11 and older have previously been reported as having ubiquitous access to such devices [34]. This may create a scenario making an unaffected PA time allocation for adolescents plausible, although a moderate inverse association between smartphone use and PA has previously been shown in a similar population [35].…”
Section: Plos Onementioning
confidence: 99%
“…A study by Raustorp et al 5 showed that there was a moderately inverse correlation between steps per day and smartphone and tablet usage in children and adolescents aged 8‐14 from six schools in south‐eastern Sweden. When the data were stratified by both sex and age groups, the association was only seen in 14‐year‐old girls.…”
Section: Correlation Between Physical Activity and Smartphone Usementioning
confidence: 99%